FACTORS ASSOCIATED WITH OWNERSHIP AND UTILIZATION OF LONG-LASTING INSECTICIDAL NETS IN RWANDA: ANALYSIS FROM NATIONAL MALARIA INDICATOR SURVEY 2017 - Murebwayire Adele, Habineza Alphonse, Habtu Michael (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Malaria remains a life-threatening disease, particularly in sub-Saharan Africa, including Rwanda. In Rwanda, Long-Lasting Insecticidal Nets (LLINs) are the primary method for malaria prevention and control. However, despite efforts to improve access, the use of LLINs remains inconsistent. In 2018, the World Health Organization reported that while 72% of households globally had at least one ITN, only 50% of at-risk individuals were using them. This study aims to assess the factors influencing the ownership and utilization of LLINs in Rwanda, using data from the 2017 Malaria Indicators Survey .This study draws on data from Rwanda’s 2017 Malaria Indicators Survey to examine the factors affecting the ownership and use of long-lasting insecticidal nets (LLINs) for malaria prevention. Data from 5,041 households were analyzed using SPSS, employing descriptive and bivariate methods to explore the relationship between socio-demographic variables and LLIN ownership and usage. Binary logistic regression was applied to identify the key factors influencing LLIN ownership and usage, with statistical significance set at p < 0.05, while adjusting for potential confounders. The results show that LLIN ownership is common in Rwanda, with 86% of households reporting they own at least one. Of these, 83% use the nets for malaria prevention. Several factors significantly influence LLIN ownership, including age, marital status, household wealth, the presence of young children, awareness of malaria, and pregnancy. For example, older individuals are more likely to own LLINs (AOR=1.93), while married individuals are even more likely (AOR=4.76), suggesting that household structure plays an important role. Wealthier households are also more likely to own LLINs (AOR range: 2.13-3.22), highlighting the impact of financial resources. Additionally, households with children under five and those with greater malaria awareness show higher ownership rates. LLIN utilization is also shaped by various factors such as marital status, wealth, rural residence, and access to information from Community Health Workers (CHWs). Married individuals are twice as likely to use LLINs (AOR=2.04), and wealthier households report higher usage (AOR=2.15). However, rural households are less likely to use LLINs (AOR=0.56), possibly due to limited access or awareness. Malaria awareness (AOR=1.46) and information from CHWs (AOR=1.66) positively influence LLIN usage, highlighting the importance of health education and targeted interventions. These findings underscore the need for focused efforts to promote LLIN use, particularly in rural areas, through education and community health initiatives. While LLIN ownership rates are relatively high, there remain disparities in utilization, highlighting the need for targeted interventions to enhance community awareness and address socio-demographic barriers.